From Opioid Pain Management to Opioid Crisis in the USA: How Can Public-Private Partnerships Help? - Bolliger, Larissa; Stevens, Hilde (Frontiers in Medicine, 2019)
The current opioid crisis in the USA arose from (at first) successful opioid pain management in three wave, starting in the 1990. By now the USA consumes fifty-six percent of the world’s opioid drugs which makes it an urgent threat to public health in the USA. Since the opioid crisis is a complex phenomenon, several stakeholders are needed to build Public-Private Partnerships between e.g. governmental institutions and the industry. Those collaborations should focus on different aspects related to the opioid crisis such as pain management process, including developing non-addictive pain medication and addressing opioid use disorders. Additionally, collaborations should cover education and training of multiple healthcare disciplines. In conclusion, despite promising collaborations, more recourses are urgently needed to tackle the opioid crisis in the USA.